Adenine Nucleotides Attenuate Murine T Cell Activation Induced by Concanavalin A or T Cell Receptor Stimulation - Shinohara, Yuria; Tsukimoto, Mitsutoshi (Frontiers in Pharmacology, 2018)
Extracellular ATP and its metabolites affect various cellular immune responses, including T cell function, but there are apparently conflicting reports concerning the effects of adenine nucleotides on T cells. For example, it has been reported that ATP-mediated activation of P2 receptor is involved in T cell activation; activation of adenosine receptors suppresses T cell function; and 1 mM ATP induces T cell death via activation of P2X7 receptor. Therefore, in this work we investigated in detail the effects of 100-250 µM ATP, ADP or AMP on murine T cell activation. First, an in vitro study showed that pretreatment of murine splenic T cells with 100-250 µM ATP, ADP, or AMP significantly suppressed the concanavalin A (ConA)-induced release of cytokines, including IL-2. This suppression was not due to induction of cell death via the P2X7 receptor or to an immunosuppressive effect of adenosine. ATP attenuated the expression of CD25, and decreased the cell proliferation ability of activated T cells. The release of IL-2 by ConA-stimulated lymphocytes was suppressed by post-treatment with ATP, as well as by pretreatment. These results suggest that exogenous ATP suppresses the activation of T cells. Secondly, we evaluated the effect of ATP in a ConA-treated mice. Treatment with ATP attenuated the increase of IL-2 concentration in the blood. Overall, these results suggest that adenine nucleotides might have potential as supplemental therapeutic agents for T cell-mediated immune diseases, by suppressing T cell activation.